Territorial dynamics and crisis on regional bus services in the State of Santa Catarina (PerCursos, 2025)
The objective of this paper is to analyze the recent territorial dynamics of intercity road passenger transportation in Santa Catarina, which is central to accessibility and mobility at regional and urban network scales. The study investigates the spatial organization of this public service and the spatial interactions it produces, highlighting its relevance for territorial integration. The paper is based on the critical theoretical framework of geographical science, based on the socio-spatial formation, a Marxist category on critical geography, combining qualitative and quantitative methods, including fieldwork. It is concluded that the service in question is central to regional integration, although it faces challenges and requires government action. Institutional innovations and effective planning are urgently needed for improved territorial logistics. Despite contradictions, such as its fragmented nature and precarious regulatory structure, the service continues to be a crucial support for the mobility of the population in Santa Catarina.
Keywords: intercity road passenger transport; spatial interactions; territorial integration; mobility; accessibility